Limited Intersystem Information Exchange Method for Heterogeneous Networks - Castanheira, D.
We consider a set of small cells deployed over a macrocell. To coexist under the same spectrum, the two systems must cooperate, so that one system can adapt to the other. In this letter, we assume that the macrocell has accurate channel information (about its channel and the cross-tier channels), which is quantized and then forwarded to the small cells. The aim is to minimize the required cross-tier information exchange rate and, at the same time, guarantee that the macrocell performance is not affected by the small cells. If the information exchange rate is adjusted as a function of the average SNR to achieve a BER target, then the required rate increases with the log of the average SNR. Therefore, we propose two adaptive approaches, where the exchange rate adapts to the instantaneous channel conditions, and show that the requirements can be exponentially reduced, i.e., only a log[log[.]] increase with the SNR is enough.